Analisis Fenomena Budaya Konsumerisme Fastfood Bagi Kalangan Generasi Z - Fiky Binti Zakiyah; Madia Mutiara Andini; Lyca Shelya Dewi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Consumerism culture is generally defined as a mindset and lifestyle that emphasizes the consumption of goods and services as the main way to achieve satisfaction, identity, and social status. The phenomenon of consumption culture encompasses various aspects that reflect how the consumption of goods and services affects the lives of individuals and society as a whole. In this study, analyze and explore the factors of consumerism that drive the popularity of fast food among Generation Z, such as ease of access, social media influence, digital marketing strategies. The results showed that Generation Z considers fast food as a practical and economical option, and is influenced by trends or promoted virally by influencers and advertisements on digital platforms. So the results show that Generation Z tends to have consumption patterns that are driven by the need for identity and self-expression, and influenced by social media trends and influencers. This research uses qualitative methods with a phenomological approach. Which data collection techniques taken by this study by observation, interviews, and documentation.